97 Interprofessional team performance: do individual professions see it differently?. (17th November 2016) - Korb, C; Lofton, L; Macgloin, H; Sampaio, H; Desai, A; Burmester, M; Lane, M
Abstract : Objective: Crisis resource management (CRM) training improves team performance, which is essential for better and safer patient care in crisis situation. Team-based self-monitoring scales can reliably assess team performance but individual professions' perception of teamwork has not been described. The Simulated InterPRofessional Team Training (SPRinT) programme at Royal Brompton Hospital runs bi monthly embedded 2 hourly in-situ simulation courses. Team performance is self-assessed by participants using TeamMonitor, a validated 9 dimension tool. We sought to assess individual medical profession' perceived team performance and according to level of training and speciality. Methods: Retrospective review of TeamMonitor data retrieved from SPRinT database from April 2014 – 2016. Team Monitor has graded scores of 0 = never/rarely, 1 = inconsistently, 2 = consistently, and NA = not applicable for each dimension. Overall and individual medical profession scores were assessed, and dimensions with 0/1 scores >50% were considered cause for concern. Questionnaires are anonymous and part of an educational program, therefore ethical approval is not necessary. Results: 44 in-situ simulation courses with recorded TeamMonitor scores were identified during the study period with data available for 308/337 participants, including 129 doctors and 134 nurse. Overall four domains were identified as cause for concern: understanding of roles, verbalising activities aloud, closed-loop communication, and loss of situational awareness. Doctors' perceived team performance scores additionally indicates cause for concern in balancing leader's authority and team members' participation, and prompting each other to attend clinical indicators, which is consistent across all speciality groups. Anaesthetists' scores causing concern also include recognition of leader, avoiding errors/complications, and shifting roles where necessary, with the latter also identified by PICU registrars. Conclusion: TeamMonitor scores vary amongst individual medical professionals. This might reflect different perception and observation of certain aspects of team performance related to one's role and behaviour in crisis situation. Our findings may help us target CRM training to these individual groups.